THE RE-OS ISOTOPE SYSTEM IN COSMOCHEMISTRY AND HIGH-TEMPERATURE GEOCHEMISTRY - Shirey S.B.; Walker R.J. (My University, 1998)
The Re-Os isotope sytem, based on the long-lived β − transition of 187 Re to 187 Os, has matured to wide use in cosmochemistry and high-temperature geochemistry. The siderophilic/chalcophilic behavior of Re and Os is different from that of the elements that comprise most other long-lived radiogenic isotope systems. Mag-matic iron meteorites (IIIAB, IIAB, IVA, and IVB) have Re-Os isochrons that indicate asteroidal core crystallization within the first 10–40 million years of Solar System evolution. Rocks from Earth's convecting mantle show generally chondritic Re/Os evolution throughout Earth history that is explained by the ad-dition of highly siderophile elements to the mantle after core formation via late accretion. Oceanic basalts have Os-isotope systematics that improve the detailed geological interpretation of extant mantle components. Some portions of ancient subcontinental lithospheric mantle are severely depleted in Re and have corre-spondingly subchondritic 187 Os/ 188 Os, indicating long-term isolation from the convecting mantle during the Archean-Proterozoic. Magmatic ore deposits have differences in initial Os isotopic composition traceable to the crustal vs mantle sources of the platinum-group elements and base metals.
Keywords: Proterozoic; Archean; Precambrian::Proterozoic; Докембрий::Протерозой; Precambrian::Archean; Докембрий::Архей